Etiology and Impact of Coinfections in Children Hospitalized With Community-Acquired Pneumonia. (8th December 2017) - Nolan, Vikki G; Arnold, Sandra R; Bramley, Anna M; Ampofo, Krow; Williams, Derek J; Grijalva, Carlos G; Self, Wesley H; Anderson, Evan J; Wunderink, Richard G; Edwards, Kathryn M; Pavia, Andrew T; Jain, Seema; et al.
Abstract : In a large study of children hospitalized with community-acquired pneumonia, virus-bacterium coinfections resulted in worse outcomes than virus-only infections. Patterns of coinfections varied with the pathogen. Abstract: Background: Recognition that coinfections are common in children with community-acquired pneumonia (CAP) is increasing, but gaps remain in our understanding of their frequency and importance. Methods: We analyzed data from 2219 children hospitalized with CAP and compared demographic and clinical characteristics and outcomes between groups with viruses alone, bacteria alone, or coinfections. We also assessed the frequency of selected pairings of codetected pathogens and their clinical characteristics. Results: A total of 576 children (26%) had a coinfection. Children with only virus detected were younger, more likely to be black, and more likely to have comorbidities such as asthma, compared with children infected with typical bacteria alone. Children with virus-bacterium coinfections had a higher frequency of leukocytosis, consolidation on chest radiography, parapneumonic effusions, intensive care unit admission, and need for mechanical ventilation and an increased length of stay, compared with children infected with viruses alone. Virus-virus coinfections were generally comparable to single-virus infections, with the exception of the need for oxygen supplementation, which was higher during the first 24 hours of hospitalization in some virus-virus pairings. Conclusions: Coinfections occurred in 26% of children hospitalized for CAP. Children with typical bacterial infections, alone or complicated by a viral infection, have worse outcomes than children infected with a virus alone.